Functional assessment of stretch hyperreflexia in children with cerebral palsy using treadmill perturbations - Flux, Eline; van der Krogt, Marjolein M.; Harlaar, Jaap; Buizer, Annemieke I.; Sloot, Lizeth H. (Journal of neuroEngineering and rehabilitation, 2021)
As hyperactive muscle stretch reflexes hinder movement in patients with central nervous system disorders, they are a common target of treatment. To improve treatment evaluation, hyperactive reflexes should be assessed during activities as walking rather than passively. This study systematically explores the feasibility, reliability and validity of sudden treadmill perturbations to evoke and quantify calf muscle stretch reflexes during walking in children with neurological disorders.
Gesehen am 09.02.2022